Developing An Interactive English For Children Textbook Oriented To Critical Thinking Skills - Ramasari, Maria; Ardayati, Ardayati (JURNAL PERSPEKTIF PENDIDIKAN, 2024)
Being able to speak another language, particularly a foreign language, will not only improve communication, but it will also make it easier to keep up with advances in science and technology. The availability of suitable textbooks is a crucial element in a learning process as an effort to achieve optimal learning. If the teaching materials and the students’ level and maturity are compatible, then the textbooks are deemed acceptable. This research’sgoal is to examine an Interactive English for Children Textbook Oriented to Critical Thinking Skills for Beginner students at SD Negeri 45 Lubuklinggau that has been adapted to meet the needs of Grade 4 Elementary School students. By modifying the ADDIE (Analysis-Design-Development-Implementation-Evaluation) development model, this form of research is considered research and development (R&D). The research participants included 20 students in the 4th grade of an elementary school in Lubuklinggau City, one elementary English teacher, and two lecturers from Bina Insan University, one of whom was an expert in learning media and the other on materials and language. Researchers used observation, interviews, questionnaires, and documentation as data collection methods. The findings revealed that while the evaluation of learning English teacher replies reached 91.66%, the level of applicability of the textbook development outcomes acquired from students’ response reached 91.05%. These findings support the notion that the end result of the construction of textbooks is highly applicable.